К чтению одного места в летописи урартского царя Аргишти I - Меликишвили, Г. A.
Melikišvili, G. А., An Interpretation of a Passage in the Chronicle of the Urartean King Argišti I.; engl. Résumé S. 274; zu UKN 127 V 41 f.